A comof-x / ma3bi2br9 composite material and a preparation method and application thereof

CN122583024BActive Publication Date: 2026-10-09QILU INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611082530.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-09
Estimated Expiration
2046-07-21

AI Technical Summary

Technical Problem

S型异质结依靠台阶式能级梯度驱动载流子转移,虽可保留部分氧化还原能力,但电荷传输驱动力有限

Benefits of technology

1.本发明采用对苯二甲酸衍生物对CoMOF-H进行后修饰处理,得CoMOF-X(X=-OCH3、-SCH3、-CN),经有机官能团修饰后,CoMOF-X(X=-OCH3、-SCH3、-CN)呈现电负性,可与MA3Bi2Br9QDs之间存在静电相互作用,增强结合能力、提高光生电子转移效率;然后将其加入至MA3Bi2Br9溶液,反应制得CoMOF-X/MA3Bi2Br9复合材料。CoMOF-X/MA3Bi2Br9复合材料中,CoMOF-X和MA3Bi2Br9QDs之间形成了Z型异质结,显著提高了光生载流子的转移效率,进而提升了催化性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122583024B_ABST
    Figure CN122583024B_ABST
Patent Text Reader

Abstract

The application discloses a CoMOF-X / MA3Bi2Br9 composite material and a preparation method and application thereof, and relates to the technical field of photocatalysts.The application adopts terephthalic acid derivatives to perform post-modification treatment on CoMOF-H to obtain CoMOF-X (X=-OCH3, -SCH3, -CN), and then the CoMOF-X is added into a MA3Bi2Br9 solution to obtain the CoMOF-X / MA3Bi2Br9 composite material through reaction, and the composite material has excellent photocatalytic CO2 reduction capacity.Through modification of organic functional groups, the CoMOF-X can be electronegative, electrostatic interaction can be formed between the CoMOF-X and MA3Bi2Br9 QDs, the combination capacity of the two is enhanced, and the photo-generated electron transfer efficiency is improved; meanwhile, a Z-type heterojunction can be formed between the CoMOF-X and the MA3Bi2Br9 QDs, the transfer efficiency of photo-generated carriers is significantly improved, and the catalytic performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalyst technology, and in particular to a CoMOF-X / MA3Bi2Br9 composite material, its preparation method, and its application. Background Technology

[0002] Converting CO2 into valuable chemicals such as CO and CH4, as well as O2, through catalytic technology can not only alleviate carbon emission pressure but also achieve the recycling of carbon resources, making it an effective way to solve energy crises and environmental problems. However, the CO2 molecule has a stable C=O bond (750 kJ / mol), which is difficult to activate and reduce during the reaction. Furthermore, the photocatalytic CO2 reduction reaction is a multi-electron transfer process, leading to low efficiency and poor stability in practical applications. Therefore, developing highly efficient CO2 reduction photocatalysts is of great significance for promoting the development of photocatalytic carbon conversion.

[0003] Metal halide perovskites (MHPs) possess unique advantages such as broad-spectrum absorption, long carrier lifetime, and high extinction coefficient, leading to their widespread application in photocatalyst preparation. However, traditional lead-based perovskites suffer from high heavy metal toxicity and poor water stability, resulting in insufficient CO2 photoreduction activity in MHP-based photocatalysts. Bismuth-based halide perovskites have attracted increasing attention due to their environmental friendliness and good water stability. Meanwhile, metal-organic frameworks (MOFs), as an emerging class of photocatalytic materials, possess well-defined structures, large specific surface areas, and tunable structures, and are widely used in hydrogen evolution, CO2 reduction, organic conversion, and environmental remediation. Although MOFs exhibit good CO2 adsorption capacity and structural tunability, their light absorption capacity is relatively weak, especially in the visible light region.

[0004] To overcome the limitations of single materials, constructing heterojunctions by combining perovskites and MOFs is an effective strategy to promote spatial separation of photogenerated carriers and synergistically improve photocatalytic efficiency. The charge transfer mechanism of heterojunctions has a decisive influence on photocatalytic performance. Although traditional Type II heterojunctions are beneficial for the spatial separation of electrons and holes, their carrier migration is often accompanied by a weakening of redox capabilities, making it difficult to meet the high reduction potential requirements of multi-electron CO2 reduction reactions. In recent years, researchers have proposed S-scheme and Z-scheme heterojunction mechanisms to overcome this bottleneck. S-scheme heterojunctions rely on step-level gradients to drive carrier transfer, which can retain some redox capabilities, but the charge transport driving force is limited. In contrast, Z-scheme heterojunctions can retain strong reduction electrons and strong oxidation holes to the greatest extent, resulting in more efficient carrier separation, stronger reduction potential, and better suitability for multi-electron CO2 reduction processes.

[0005] Post-synthetic modification (PSM) refers to the technique of chemically modifying materials after synthesis without destroying their original structure. This strategy can precisely introduce functional groups into MOFs and regulate surface electronic states, interfacial interactions, and band structure, making it an important means of optimizing the performance of MOF / perovskite heterojunctions. Based on this, using MA3Bi2Br9QDs and MOFs as raw materials, a strong electronic coupling interaction is established between them through a post-synthetic modification strategy, thereby constructing a Z-shaped heterojunction with atomically close contact in situ. This preparation of a highly efficient, stable, and environmentally friendly CO2 photoreduction catalyst has significant scientific and practical application value. Summary of the Invention

[0006] To address the aforementioned limitations of existing technologies, the present invention aims to provide a CoMOF-X / MA3Bi2Br9 composite material, its preparation method, and its applications. The present invention employs a terephthalic acid derivative to post-modify CoMOF-H, yielding CoMOF-X (X = -OCH3, -SCH3, -CN); this is then added to an MA3Bi2Br9 solution to react and prepare the CoMOF-X / MA3Bi2Br9 composite material, which exhibits excellent photocatalytic CO2 reduction capability. The present invention, through modification of organic functional groups, enables CoMOF-X to become electronegative, forming an electrostatic interaction with MA3Bi2Br9 QDs, enhancing their binding ability and improving the photogenerated electron transfer efficiency; furthermore, a Z-shaped heterojunction can be formed between CoMOF-X and MA3Bi2Br9 QDs, significantly improving the transfer efficiency of photogenerated carriers, thereby enhancing catalytic performance.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a CoMOF-X / MA3Bi2Br9 composite material, comprising the following steps: (1) Disperse terephthalic acid in a mixed solvent, then add CoCl2·6H2O, mix by sonication to obtain a mixed solution; heat the mixed solution to carry out the reaction, cool after the reaction, centrifuge and collect the precipitate, wash and dry to obtain CoMOF-H; (2) Add the terephthalic acid derivative to KOH solution, adjust the pH to obtain a terephthalic acid derivative solution; add CoMOF-H to the terephthalic acid derivative solution, heat to carry out the reaction, collect the precipitate after the reaction, wash and dry to obtain CoMOF-X; (3) CoMOF-X was added to MA3Bi2Br9 solution, ultrasonically treated and stirred to carry out the reaction. After the reaction, the precipitate was collected by centrifugation, dried, and CoMOF-X / MA3Bi2Br9 composite material was obtained.

[0008] Preferably, in step (1), the mixed solvent is a mixture of N,N-dimethylformamide, ethanol and water in a volume ratio of (30-35):(1.5-2.5):(1.5-2.5).

[0009] Preferably, in step (1), the ratio of terephthalic acid, N,N-dimethylformamide in the mixed solvent, and CoCl2·6H2O is (0.7-0.8) mmol: (30-35) mL: (0.7-0.8) mmol.

[0010] Preferably, in step (1), the heating temperature is 130-150℃ and the reaction time is 47-49h.

[0011] Preferably, in step (1), the washing operation is as follows: wash with N,N-dimethylformamide 2-4 times, and then wash with anhydrous ethanol 2-4 times.

[0012] Preferably, in step (1), the drying temperature is 50-70℃ and the drying time is 11-13h.

[0013] Preferably, in step (2), the terephthalic acid derivative is one or more of 2-methoxyterephthalic acid, 2,5-bis(methylthio)terephthalic acid, and 2-cyanoterephthalic acid.

[0014] Preferably, in step (2), the mass fraction of the KOH solution is 3%-5%.

[0015] Preferably, in step (2), the ratio of terephthalic acid derivative, KOH solution and CoMOF-H is (70-90) mg: 2 mL: (15-25) mg.

[0016] Preferably, in step (2), the pH is adjusted to 7 using hydrochloric acid with a concentration of 1 mol / L.

[0017] Preferably, in step (2), the heating temperature is 80-90℃ and the reaction time is 20-26h.

[0018] Preferably, in step (2), the washing operation is: washing with N,N-dimethylformamide and methanol 2-4 times in sequence.

[0019] Preferably, in step (2), the drying method is vacuum drying, the drying temperature is 50-70℃, and the drying time is 11-13h.

[0020] Preferably, in step (3), the MA3Bi2Br9 solution is prepared by mixing MA3Bi2Br9QDs and ethyl acetate at a ratio of (15-25) mg: 5 mL.

[0021] Furthermore, MA3Bi2Br9QDs were prepared by the following method: (a) Mix ammonium bromide (MABr), octadecene (ODE) and oleic acid (OA) at a ratio of (0.3-0.35) g: 20 mL: (1-1.5) mL, heat to 110-130 °C under an argon atmosphere and hold for 1 h, then raise the temperature to 130-150 °C and hold for 25-35 min to obtain the MABr precursor solution; (b) Bismuth bromide (BiBr3), octadecene (ODE), oleic acid (OA) and oleylamine (OM) were mixed at a ratio of (0.6-0.8) g: (45-55) mL: 5 mL: 5 mL, heated to 110-130 °C under an argon atmosphere and held for 1 h, then heated to 160-180 °C and held for 8-12 min to obtain Bi precursor solution; (c) Add the MABr precursor solution to the Bi precursor solution and cool to terminate the reaction; after adding ethyl acetate, centrifuge, collect the precipitate, and purify to obtain MA3Bi2Br9QDs; The volume ratio of MABr precursor solution to Bi precursor solution is 4 mL: (55-60) mL.

[0022] Furthermore, in step (c), the washing process is as follows: washing with n-hexane and ethyl acetate in sequence, 2-4 times each time.

[0023] Preferably, in step (3), the mass ratio of MA3Bi2Br9QDs in CoMOF-X and MA3Bi2Br9 solution is 1:(8-12).

[0024] Preferably, in step (3), the ultrasonic treatment time is 5-15 min.

[0025] Preferably, in step (3), the stirring time is 11-13 hours.

[0026] In a second aspect, the present invention provides a CoMOF-X / MA3Bi2Br9 composite material prepared by the above-described preparation method.

[0027] In a third aspect, the present invention provides the application of the above-described CoMOF-X / MA3Bi2Br9 composite material in photocatalytic CO2 reduction.

[0028] As a preferred method, the specific application method is as follows: the above-mentioned CoMOF-X / MA3Bi2Br9 composite material is added to the reactor as a catalyst, deionized water is used as a solvent and proton source, CO2 gas is introduced, and photocatalytic CO2 reduction is carried out under light irradiation.

[0029] Furthermore, the ratio of CoMOF-X / MA3Bi2Br9 composite material to deionized water is (0.5-1.5) mg: 20 μL; the CO2 gas introduction rate is 10-30 mL / min, and the introduction time is 15-25 min.

[0030] Furthermore, the light intensity is 250-350 mW·cm². -2 The light source is a xenon lamp.

[0031] The beneficial effects of this invention are: 1. This invention employs terephthalic acid derivatives to post-modify CoMOF-H, yielding CoMOF-X (X = -OCH3, -SCH3, -CN). After modification with organic functional groups, CoMOF-X (X = -OCH3, -SCH3, -CN) exhibits electronegativity and can interact electrostatically with MA3Bi2Br9QDs, enhancing binding ability and improving photogenerated electron transfer efficiency. Then, it is added to an MA3Bi2Br9 solution to prepare a CoMOF-X / MA3Bi2Br9 composite material. In the CoMOF-X / MA3Bi2Br9 composite material, a Z-shaped heterojunction is formed between CoMOF-X and MA3Bi2Br9QDs, significantly improving the transfer efficiency of photogenerated carriers and thus enhancing catalytic performance.

[0032] The CoMOF-X / MA3Bi2Br9 composite material prepared by this invention exhibits excellent photocatalytic CO2 reduction ability. Specifically, when used as a catalyst, the photocatalytic reduction rate of CO2 to CO can reach up to 152.6 µmol / (g·h) with a selectivity of up to 100%.

[0033] Furthermore, the preparation process of CoMOF-X / MA3Bi2Br9 composite material is simple, convenient, and yields high efficiency, and can produce photocatalysts with high activity and selectivity. It is a general and convenient method for preparing composite photocatalysts.

[0034] 2. MA3Bi2Br9QDs, a bismuth-based lead-free perovskite, can completely replace traditional lead-based perovskites. It has no heavy metal toxicity and meets environmental protection and biosafety requirements. At the same time, MA3Bi2Br9QDs has better water resistance and light stability than traditional lead-based perovskites, making it more suitable for actual catalytic environments. Attached Figure Description

[0035] Figure 1X-ray diffraction patterns of CoMOF-H / MA3Bi2Br9 composites, CoMOF-OCH3 / MA3Bi2Br9 composites, CoMOF-SCH3 / MA3Bi2Br9 composites, CoMOF-CN / MA3Bi2Br9 composites, and simulated CoMOF and MA3Bi2Br9 QDs; Figure 2 Zeta potential diagrams of MA3Bi2Br9, CoMOF-OCH3, CoMOF-SCH3, and CoMOF-CN; Figure 3 Super-resolution transmission electron microscopy (SEM) images of CoMOF-H / MA3Bi2Br9, CoMOF-OCH3 / MA3Bi2Br9, CoMOF-SCH3 / MA3Bi2Br9, and CoMOF-CN / MA3Bi2Br9; where a is an SEM image of CoMOF-H / MA3Bi2Br9; b is an SEM image of CoMOF-OCH3 / MA3Bi2Br9; c is an SEM image of CoMOF-SCH3 / MA3Bi2Br9; and d is an SEM image of CoMOF-CN / MA3Bi2Br9. Figure 4 UV-Vis absorption spectra of CoMOF-H, CoMOF-OCH3, CoMOF-SCH3, and CoMOF-CN; Figure 5 Band structure diagrams of CoMOF-OCH3 and MA3Bi2Br9; Figure 6 X-ray photoelectron spectra of CoMOF-OCH3 / MA3Bi2Br9 composite material under light and dark conditions; where a is the X-ray photoelectron spectrum of Co 2p and b is the X-ray photoelectron spectrum of Br 3d. Figure 7 : CO generation rate diagram of the photocatalytic CO2 reduction to CO process of CoMOF-OCH3 / MA3Bi2Br9, CoMOF-SCH3 / MA3Bi2Br9, CoMOF-CN / MA3Bi2Br9, CoMOF-H / MA3Bi2Br9, MA3Bi2Br9QDs, and CoMOF-H. Detailed Implementation

[0036] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0037] This invention is a further study based on the inventor's previous work on "Preparation of metal-organic framework and graphdiyne-based composite materials and their photo / electrocatalytic CO2 reduction performance".

[0038] First, although bismuth-based halide perovskites have attracted increasing attention due to their environmental friendliness and good water stability, all-inorganic bismuth-based halide perovskites (such as Cs3Bi2Br9QDs) exhibit high internal defect density, complex surface states, poor energy level modulation flexibility, easy carrier capture by defects, and low charge separation efficiency. Furthermore, they show a significant tendency for particle aggregation and weak interface modifiability, making it difficult to form strong electronic coupling interfaces with MOFs, thus limiting the improvement of heterojunction photocatalytic performance. In contrast, organic-inorganic hybrid MA3Bi2Br9QDs (MA... + The organic methylamine cation (MA3Bi2Br9QDs) possesses significant structural advantages: it can act as a structure modifier, effectively passivating surface defects and reducing non-radiative recombination losses; simultaneously, the flexible organic chain endows the material with good energy level tunability and interfacial affinity, facilitating atomic-level close contact with MOFs, which is beneficial for the rapid separation and transport of photogenerated carriers, making it more suitable for constructing efficient Z-type heterojunction photocatalytic systems. However, MA3Bi2Br9QDs still face similar problems to MHPs, namely, a lack of effective catalytic sites and a tendency to aggregate during the catalytic reaction.

[0039] Secondly, previous studies used -NH2, -OH, and -F groups to modify MOFs. However, experimental analysis revealed that these functional groups had poor interfacial compatibility with MA3Bi2Br9QDs, making it difficult to exert synergistic catalytic advantages. The strong electron-donating effect of amino groups (-NH2) easily leads to excessively high electron density on the MOF surface, resulting in electrostatic repulsion with the electronegative MA3Bi2Br9QDs, loose interfacial bonding, and weak electronic coupling. Hydroxyl groups (-OH) are prone to deprotonation, have unstable surface charge, and have weak and reversible interfacial interactions with MA3Bi2Br9QDs, making it difficult to form stable heterojunctions. Although fluorine groups (-F) are electron-withdrawing groups, their excessive electronegativity and small steric hindrance easily cause excessive compression of the interfacial electron cloud, severe band mismatch, and high electron transfer resistance. At the same time, they lack active sites that can activate CO2, resulting in low activity and insufficient stability of the composite catalyst.

[0040] Based on this, the present invention provides a CoMOF-X / MA3Bi2Br9 composite material. Novel functional groups such as -OCH3, -SCH3, and -CN are used to modify CoMOF during post-synthesis, achieving precise interfacial matching and performance synergy with MA3Bi2Br9QDs. Specifically, the methoxy group (-OCH3) possesses both moderate electron-donating properties and strong electronegativity, resulting in optimal electronegativity on the CoMOF surface, forming a moderately strong electrostatic interaction with MA3Bi2Br9QDs, leading to stable interfacial bonding and strong electronic coupling. The sulfur atom of the methylthio group (-SCH3) can form secondary coordination with Co sites, strengthening interfacial electronic coupling. The cyano group (-CN) has strong electron-withdrawing ability, allowing precise control of MOF energy level positions and achieving ideal band crossing with MA3Bi2Br9QDs.

[0041] In this invention, a Z-type heterojunction is formed between CoMOF-X and MA3Bi2Br9QDs. Compared with the S-type heterojunction, the Z-type heterojunction can significantly improve the transfer efficiency of photogenerated carriers, thereby enhancing the catalytic performance.

[0042] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0043] The experimental materials used in the embodiments of this invention are all conventional experimental materials in the art and can be purchased through commercial channels.

[0044] In this invention, the CAS number of methyl bromide is 6876-37-5, the CAS number of octadecene is 112-88-9, the CAS number of oleic acid is 112-80-1, the CAS number of bismuth bromide is 7787-58-8, the CAS number of oleylamine is 112-90-3, the CAS number of 2-methoxyterephthalic acid is 5156-00-3, the CAS number of 2,5-bis(methylthio)terephthalic acid is 2097747-77-6, and the CAS number of 2-cyanoterephthalic acid is 1262725-70-1.

[0045] Example 1: (1) Mix 32 mL of N,N-dimethylformamide (DMF), 2 mL of ethanol and 2 mL of deionized water to obtain a mixed solution; weigh 0.75 mmol of terephthalic acid (BDC) and disperse it in the above mixed solution, then add 0.75 mmol of CoCl2·6H2O, and mix by sonication to obtain a mixed solution; The mixture was transferred to a high-pressure reactor and heated to 140°C for 48 hours. After the reaction, the mixture was cooled, centrifuged, and the precipitate was collected. The precipitate was washed three times with N,N-dimethylformamide (DMF) and ethanol, and then dried under vacuum at 60°C for 12 hours to obtain CoMOF-H. (2) Dissolve 80 mg of 2-methoxyterephthalic acid in 2 mL of 4% KOH solution, and adjust the pH to 7 with 1 mol / L hydrochloric acid to obtain a terephthalic acid derivative solution; 20 mg of CoMOF-H was added to the above solution and heated to 85 °C for 24 h. After the reaction, the precipitate was collected, washed three times with N,N-dimethylformamide and methanol, and then dried under vacuum at 60 °C for 12 h to obtain CoMOF-OCH3. (3) Add 0.32 g of ammonium bromide (MABr), 20 mL of octadecene (ODE) and 1.2 mL of oleic acid (OA) to a three-necked flask, mix them, heat to 120°C under an argon atmosphere and keep warm for 1 h, then heat to 140°C and heat for 30 min to obtain the MABr precursor solution. Take another three-necked flask, mix 0.72g bismuth bromide (BiBr3), 50mL octadecene (ODE), 5mL oleylamine (OM) and 5mL oleic acid (OA), heat to 120℃ under argon atmosphere and keep at that temperature for 1h, then raise the temperature to 170℃ and keep at that temperature for 10min to obtain Bi precursor solution; 4 mL of the above MABr precursor solution was quickly injected into 60 mL of Bi precursor solution, and the mixture was rapidly cooled in liquid nitrogen. Ethyl acetate was added to the reaction liquid, and the yellow precipitate was collected by centrifugation. The precipitate was washed three times with n-hexane and ethyl acetate to obtain MA3Bi2Br9QDs. (4) Place 20 mg of MA3Bi2Br9QDs in 5 mL of ethyl acetate and disperse by ultrasonication to obtain MA3Bi2Br9 solution; add 2 mg of CoMOF-OCH3 to the above MA3Bi2Br9 solution, sonicate for 10 min using a cell wall disruptor, stir overnight for 12 h, centrifuge and collect the precipitate, and vacuum dry at 40°C for 12 h to obtain CoMOF-OCH3 / MA3Bi2Br9 composite material.

[0046] Example 2: The difference between this embodiment and Embodiment 1 is that 2,5-bis(methylthio)terephthalic acid is used instead of 2-methoxyterephthalic acid to prepare the CoMOF-SCH3 / MA3Bi2Br9 composite material.

[0047] Example 3: The difference between this embodiment and Embodiment 1 is that 2-cyanoterephthalic acid is used instead of 2-methoxyterephthalic acid to prepare the CoMOF-CN / MA3Bi2Br9 composite material.

[0048] Comparative Example 1: The difference between this comparative example and Example 1 is that no post-modification was performed on CoMOF-H. Specifically: CoMOF-H was prepared according to the method in Example 1; 20 mg of MA3Bi2Br9 QDs were placed in 5 mL of ethyl acetate and ultrasonically dispersed to obtain an MA3Bi2Br9 solution; 2 mg of CoMOF-H was added to the above MA3Bi2Br9 solution, and the mixture was ultrasonically treated for 10 min using a cell wall disruptor, stirred overnight, centrifuged and the precipitate was collected, and vacuum dried at 40°C for 12 h to obtain the CoMOF-H / MA3Bi2Br9 composite material.

[0049] Experimental Example 1: Structural Characterization 1. X-ray diffraction analysis The CoMOF-H / MA3Bi2Br9 composite material prepared in Comparative Example 1, the CoMOF-OCH3 / MA3Bi2Br9 composite material prepared in Example 1, the CoMOF-SCH3 / MA3Bi2Br9 composite material prepared in Example 2, and the CoMOF-CN / MA3Bi2Br9 composite material prepared in Example 3 were used as samples for X-ray diffraction analysis. The results are as follows: Figure 1 As shown. Since MA3Bi2Br9QDs does not have an official independent JCPDS / ICDD standard PDF number, its XRD diffraction data are from the literature Angew. Chem. Int. Ed., 2016, 55, 15012-15016.

[0050] Depend on Figure 1 As can be seen, in the X-ray diffraction patterns of the CoMOF-X / MA3Bi2Br9 composite materials (X=-H, -OCH3, -SCH3, -CN), diffraction peaks of both CoMOF-X and MA3Bi2Br9 QDs can be observed, proving the successful composite formation. Furthermore, the main peak positions of CoMOF-X modified with different substituents show high consistency, indicating that the introduction of substituents did not alter the main framework and crystal topology of CoMOF itself.

[0051] 2. Zeta potential analysis The MA3Bi2Br9 solution prepared in step (4) of Example 1, the CoMOF-OCH3 prepared in step (2) of Example 1, the CoMOF-SCH3 prepared in step (2) of Example 2, and the CoMOF-CN prepared in step (2) of Example 3 were used as samples and labeled as MA3Bi2Br9, CoMOF-OCH3, CoMOF-SCH3, and CoMOF-CN, respectively. Zeta potential analysis was performed on the above samples, and the results are as follows. Figure 2 As shown.

[0052] Depend on Figure 2It can be seen that CoMOF-OCH3, CoMOF-SCH3, and CoMOF-CN are all electronegative, while MA3Bi2Br9 is electronegative. This indicates that CoMOF-X and MA3Bi2Br9 can form an electrostatic interaction, and the interaction force between them is stronger, which is conducive to electron transfer.

[0053] 3. Ultra-high resolution transmission electron microscopy analysis The following composite materials were used as samples: CoMOF-H / MA3Bi2Br9 (Comparative Example 1), CoMOF-OCH3 / MA3Bi2Br9 (Example 1), CoMOF-SCH3 / MA3Bi2Br9 (Example 2), and CoMOF-CN / MA3Bi2Br9 (Example 3), respectively labeled as CoMOF-H / MA3Bi2Br9, CoMOF-OCH3 / MA3Bi2Br9, CoMOF-SCH3 / MA3Bi2Br9, and CoMOF-SCH3 / MA3Bi2Br9. Ultra-high resolution transmission electron microscopy (UHTEM) analysis was performed on these samples, and the results are as follows: Figure 3 As shown.

[0054] Depend on Figure 3 a- Figure 3 As can be seen from d, CoMOF-X (X=-H, -OCH3, -SCH3, -CN) has a layered structure, and MA3Bi2Br9QDs are uniformly distributed in CoMOF-X.

[0055] 4. Ultraviolet-Vis absorption spectroscopy analysis The CoMOF-H prepared in step (1) of Example 1, the CoMOF-OCH3 prepared in step (2) of Example 1, the CoMOF-SCH3 prepared in step (2) of Example 2, and the CoMOF-CN prepared in step (2) of Example 3 were used as samples and denoted as CoMOF-H, CoMOF-OCH3, CoMOF-SCH3, and CoMOF-CN, respectively. The above samples were subjected to UV-Vis absorption spectroscopy analysis, and the results are as follows: Figure 4 As shown.

[0056] Depend on Figure 4 It can be seen that CoMOF-X (X=-OCH3, -SCH3, -CN) mainly absorbs ultraviolet and weak visible light. Compared with CoMOF-H, the light absorption capacity of CoMOF-X (X=-OCH3, -SCH3, -CN) is enhanced after modification with ligands (-OCH3, -SCH3, -CN), which indirectly proves the successful modification of the ligands.

[0057] 5. Band Structure Analysis The MA3Bi2Br9 solution prepared in step (4) of Example 1 and the CoMOF-OCH3 prepared in step (2) of Example 1 were used as samples, denoted as MA3Bi2Br9 and CoMOF-OCH3, respectively; conduction band energy level tests were performed on the above samples, and the results are as follows. Figure 5 As shown.

[0058] Depend on Figure 5 It can be seen that the CB position of MA3Bi2Br9 and CoMOF-OCH3 has a more negative reduction potential than that of CO2 / HCOOH, CO2 / CO, and CO2 / CH4, while the VB valence band position is more positive than that of H2O / O2 (0.81 V vs. NHE). These results demonstrate the theoretical feasibility of their photocatalytic CO2 reduction and H2O oxidation. Furthermore, the interleaved band structure between the two indicates that the CoMOF-OCH3 / MA3Bi2Br9 composite material may form a type II or Z-type heterojunction under light irradiation.

[0059] 6. X-ray photoelectron spectroscopy analysis X-ray photoelectron spectroscopy analysis was performed on the CoMOF-OCH3 / MA3Bi2Br9 composite material prepared in Example 1, and the results are as follows: Figure 6 As shown.

[0060] Depend on Figure 6 As shown in figures a and b, compared to the dark state, the binding energy of Br 3d shifts towards higher energies under illumination, indicating that MA3Bi2Br9QDs in the CoMOF-OCH3 / MA3Bi2Br9 composite material loses electrons. Conversely, the binding energy of Co 2p shifts towards lower energies under illumination, indicating that CoMOF-OCH3 in the CoMOF-OCH3 / MA3Bi2Br9 composite material gains electrons. These results demonstrate that when illuminated, MA3Bi2Br9QDs and CoMOF-OCH3 in the CoMOF-OCH3 / MA3Bi2Br9 composite material form a Z-shaped heterojunction.

[0061] Experimental Example 2: Photocatalytic CO2 Reduction Performance The CoMOF-H / MA3Bi2Br9 composite material prepared in Comparative Example 1, the CoMOF-CN / MA3Bi2Br9 composite material prepared in Example 3, the CoMOF-SCH3 / MA3Bi2Br9 composite material prepared in Example 2, the CoMOF-OCH3 / MA3Bi2Br9 composite material prepared in Example 1, the CoMOF-H prepared in step (1) of Example 1, and the MA3Bi2Br9QDs prepared in step (3) of Example 1 were respectively used as samples and were denoted as CoMOF-H / MA3Bi2Br9, CoMOF-CN / MA3Bi2Br9, CoMOF-SCH3 / MA3Bi2Br9, CoMOF-OCH3 / MA3Bi2Br9, CoMOF-H, and MA3Bi2Br9QDs. Weigh 1 mg of the above sample and place it in a quartz tube. Add 20 μL of deionized water as a solvent and proton source. Do not add any photosensitizer or electron sacrificial agent. Seal the quartz tube. Pass high-purity CO2 into the quartz tube to remove O2 and other gases. Once a CO2 atmosphere is formed in the quartz tube, continue to pass CO2 gas at a rate of 20 L / min for 20 min. Perform a photocatalytic CO2 reduction reaction under illumination for 4 h. After the reaction, collect the gaseous sample and perform quantitative analysis using gas chromatography to calculate the CO generation rate. The results are as follows: Figure 7 As shown.

[0062] Depend on Figure 7 It is known that CoMOF-H has weak visible light absorption and fast recombination of photogenerated carriers, and therefore does not have the ability to reduce CO2 to CO. MA3Bi2Br9QDs, CoMOF-H / MA3Bi2Br9, CoMOF-CN / MA3Bi2Br9, CoMOF-SCH3 / MA3Bi2Br9, and CoMOF-OCH3 / MA3Bi2Br9 can all reduce CO2 to CO, with generation rates of 3.8, 40.2, 86.3, 124.6, and 152.6 µmol / (g·h), respectively. CoMOF-OCH3 / MA3Bi2Br9 exhibits the best catalytic performance.

[0063] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing a CoMOF-X / MA3Bi2Br9 composite material, characterized in that, Includes the following steps: (1) Disperse terephthalic acid in a mixed solvent, then add CoCl2·6H2O, mix by sonication to obtain a mixed solution; heat the mixed solution to carry out the reaction, cool after the reaction, centrifuge and collect the precipitate, wash and dry to obtain CoMOF-H; (2) Add the terephthalic acid derivative to the KOH solution, adjust the pH, and obtain the terephthalic acid derivative solution; CoMOF-H was added to a solution of terephthalic acid derivatives, and the mixture was heated to carry out the reaction. After the reaction, the precipitate was collected, washed, and dried to obtain CoMOF-X. The terephthalic acid derivatives were one or more of 2-methoxyterephthalic acid, 2,5-bis(methylthio)terephthalic acid, and 2-cyanoterephthalic acid. (3) CoMOF-X was added to MA3Bi2Br9 solution, ultrasonicated and stirred to react, centrifuged after reaction, precipitate was collected and dried to obtain CoMOF-X / MA3Bi2Br9 composite material; In the CoMOF-X / MA3Bi2Br9 composite material, a Z-shaped heterojunction is formed between CoMOF-X and MA3Bi2Br9 QDs.

2. The preparation method of the CoMOF-X / MA3Bi2Br9 composite material as described in claim 1, characterized in that, In step (1), the mixed solvent is a mixture of N,N-dimethylformamide, ethanol and water in a volume ratio of (30-35):(1.5-2.5):(1.5-2.5); the ratio of terephthalic acid, N,N-dimethylformamide in the mixed solvent and CoCl2·6H2O is (0.7-0.8) mmol:(30-35) mL:(0.7-0.8) mmol.

3. The method for preparing the CoMOF-X / MA3Bi2Br9 composite material as described in claim 1, characterized in that, In step (1), the heating temperature is 130-150℃ and the reaction time is 47-49h; the drying temperature is 50-70℃ and the drying time is 11-13h.

4. The preparation method of the CoMOF-X / MA3Bi2Br9 composite material as described in claim 1, characterized in that, In step (2), the ratio of terephthalic acid derivative, KOH solution and CoMOF-H is (70-90) mg: 2 mL: (15-25) mg.

5. The method for preparing the CoMOF-X / MA3Bi2Br9 composite material as described in claim 1, characterized in that, In step (2), the heating temperature is 80-90℃ and the reaction time is 20-26h.

6. The method for preparing the CoMOF-X / MA3Bi2Br9 composite material as described in claim 1, characterized in that, In step (3), the MA3Bi2Br9 solution is prepared by mixing MA3Bi2Br9 QDs and ethyl acetate at a ratio of (15-25) mg: 5 mL.

7. The method for preparing the CoMOF-X / MA3Bi2Br9 composite material as described in claim 6, characterized in that, MA3Bi2Br9QDs were prepared by the following method: (a) Mix ammonium bromide, octadecene and oleic acid at a ratio of (0.3-0.35) g: 20 mL: (1-1.5) mL, heat to 110-130 °C under argon atmosphere and hold for 1 h, then raise the temperature to 130-150 °C and hold for 25-35 min to obtain MABr precursor solution; (b) Bismuth bromide, octadecene, oleic acid and oleylamine were mixed at a ratio of (0.6-0.8) g: (45-55) mL: 5 mL: 5 mL, heated to 110-130 °C under an argon atmosphere and held for 1 h, then heated to 160-180 °C and held for 8-12 min to obtain Bi precursor solution; (c) Add the MABr precursor solution to the Bi precursor solution and cool to terminate the reaction; add ethyl acetate to the liquid after the reaction, centrifuge and collect the precipitate, and purify to obtain MA3Bi2Br9 QDs; The volume ratio of MABr precursor solution to Bi precursor solution is 4 mL: (55-60) mL.

8. The method for preparing the CoMOF-X / MA3Bi2Br9 composite material as described in claim 1, characterized in that, The mass ratio of MA3Bi2Br9 QDs in CoMOF-X and MA3Bi2Br9 solutions was 1:(8-12); the ultrasonic treatment time was 5-15 min and the stirring time was 11-13 h.

9. The CoMOF-X / MA3Bi2Br9 composite material prepared by the preparation method according to any one of claims 1-8.

10. The application of the CoMOF-X / MA3Bi2Br9 composite material according to claim 9 in photocatalytic CO2 reduction.

Citation Information

Patent Citations

  • Preparation method of Bi-based perovskite quantum dot material

    CN106433619A

  • Co-MOF / Bi2MoO6 composite photocatalyst as well as preparation method and application thereof

    CN118268041A